Unraveling the features of somatic transposition in the Drosophila intestine - Siudeja, Katarzyna (EMBO J, 2021)
Transposable elements (TEs) play a significant role in evolution, contributing to genetic variation. However, TE mobilization in somatic cells is not well understood. Here, we address the prevalence of transposition in a somatic tissue, exploiting the Drosophila midgut as a model. Using whole‐genome sequencing of in vivo clonally expanded gut tissue, we have mapped hundreds of high‐confidence somatic TE integration sites genome‐wide. We show that somatic retrotransposon insertions are associated with inactivation of the tumor suppressor Notch, likely contributing to neoplasia formation. Moreover, applying Oxford Nanopore long‐read sequencing technology we provide evidence for tissue‐specific differences in retrotransposition. Comparing somatic TE insertional activity with transcriptomic and small RNA sequencing data, we demonstrate that transposon mobility cannot be simply predicted by whole tissue TE expression levels or by small RNA pathway activity. Finally, we reveal that somatic TE insertions in the adult fly intestine are enriched in genic regions and in transcriptionally active chromatin. Together, our findings provide clear evidence of ongoing somatic transposition in Drosophila and delineate previously unknown features underlying somatic TE mobility in vivo.